Fluorescence in situ hybridization (FISH) screening for the 22q11.2 deletion in patients with clinical features of velocardiofacial syndrome but without cardiac anomalies - Paula Sandrin-Garcia (Genetics and Molecular Biology, 2007)
The velocardiofacial syndrome (VCFS), a condition associated with 22q11.2 deletions, is characterized by a typical facies, palatal anomalies, learning disabilities, behavioral disturbances and cardiac defects. We investigated the frequency of these chromosomal deletions in 16 individuals with VCFS features who presented no cardiac anomalies, one of the main characteristics of VCFS. Fluorescent in situ hybridization (FISH) with the N25 (D22S75; 22q11.2) probe revealed deletions in ten individuals (62%). Therefore, even in the absence of cardiac anomalies testing for the 22q11.2 microdeletions in individuals showing other clinical features of this syndrome is recommended.